2020
DOI: 10.20882/adicciones.1321
|View full text |Cite
|
Sign up to set email alerts
|

Trastorno por uso de cocaína y depresión: Cuando el diagnóstico clínico no es suficiente

Abstract: Antecedentes: El consumo de cocaína es un creciente problema de salud en todo el mundo. Además, los pacientes con trastorno por consumo de cocaína (TCC) presentan una alta comorbilidad con el trastorno depresivo mayor (TDM). Estos pacientes pueden presentar dos tipos de TDM: trastorno depresivo mayor primario (TDM-P) y trastorno depresivo mayor inducido por cocaína (TDM-IC). El objetivo de este estudio es evaluar las diferencias en la sintomatología depresiva (TDM-P vs. TDM-IC) en los pacientes con TCC para me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The high medical comorbidity found among AI-MD patients may explain this significant difference related to weight criteria [ 70 , 71 ] although we have not detected this association in our sample. Other authors have found different criteria between Primary and Induced depression associated with cocaine use disorder [ 72 ]; however, these authors found more “weight changes” in the primary depression group compared to induced depression group. In contrast, Primary MD patients met more criteria related to anhedonia, loss of concentration and recurrent thoughts of death.…”
Section: Discussionmentioning
confidence: 93%
“…The high medical comorbidity found among AI-MD patients may explain this significant difference related to weight criteria [ 70 , 71 ] although we have not detected this association in our sample. Other authors have found different criteria between Primary and Induced depression associated with cocaine use disorder [ 72 ]; however, these authors found more “weight changes” in the primary depression group compared to induced depression group. In contrast, Primary MD patients met more criteria related to anhedonia, loss of concentration and recurrent thoughts of death.…”
Section: Discussionmentioning
confidence: 93%
“…In clinical practice, the co-occurrence of substance use hinders both the diagnosis of depressive symptoms and the differentiation between primary depressive and cocaine-induced episodes. Indeed, such a distinction could prove crucial in improving diagnostics and treatment, and therefore the prognoses [2,3]. Accordingly, there is a growing interest in putative biomarker research that enhances a better approach to this comorbid pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the elevated prevalence of psychotic and personality disorders, the predominant focus of studies within the context of cocaine has been on mood disorders, specifically major depression [ 5 , 42 ]. In particular, dual diagnosis with SCZ and APD exacerbates the severity of these disorders, such as difficulties in decision-making, and compromises the daily functioning of these patients, and complicates the course and treatment of CUD [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine is one of the most commonly used psychoactive substances in young adults, and its use increases the incidence of severe clinical complications, including a significant loss of efficacy of current psychopharmacological interventions [1,2]. Repeated use of cocaine can lead to cocaine use disorder (CUD), which is associated with an elevated prevalence of comorbid mental disorders [3][4][5]. The coexistence of substance use disorder and additional psychiatric disorders is referred to as dual diagnosis, and the most common comorbidities among individuals with CUD are mood disorders, anxiety, psychotic disorders, and personality disorders [6,7].…”
Section: Introductionmentioning
confidence: 99%